Some Notes on Political Parties and Democracy in Indonesia - Satya Arinanto (Novateur Publications, 2022)
From a theoretical standpoint, the state is viewed as, among others, an organization of power. This is due to the fact that within a state, we always encounter centers of power, either at the superstructural level (manifested in political parties and state institutions), as well as at the infrastructural level, which consist of (1) political parties, (2) interest groups, (3) pressure groups, (4) political communication instruments, and (5) political figures.